Higher education as a stage in competence development - Jarecki, Wojciech (Annales. Etyka w Życiu Gospodarczym, 2019)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-font-style: italic; mso-ansi-language: PL; mso-bidi-language: AR-SA;">Higher education should enable students to raise their qualifications, and particularly acquire new knowledge, develop their interests, or learn to think critically. As for economics students, tertiary education should provide them with an opportunity to find and follow their career path. Having this in mind, the author of the present paper discusses factors contributing to economics students’ involvement in raising their qualifications. The main aim is to state why they have become less involved in doing so and particularly in acquiring new knowledge.<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-font-style: italic; mso-ansi-language: PL; mso-bidi-language: AR-SA;">